Preferred place of death and end-of-life care for adult cancer patients in Iran: A cross-sectional study - Fereidouni, Armin; Salesi, Mahmood; Rassouli, Maryam; Hosseinzadegan, Fariba; Javid, Mohammad; Karami, Maryam; Elahikhah, Maryam; Barasteh, Salman (Frontiers in Oncology, 2022)
Background More than 50,000 deaths in terms of cancer occur annually in Iranian hospitals. Determining the preferred place of end-of-life care and death for cancer patients in Iran is a quality marker for good end-of-life care and good death. The purpose of this study was to determine the preferred place of end-of-life care and death in cancer patients. Method In 2021, the current descriptive cross-sectional investigation was carried out. Using the convenience sample approach, patients were chosen from three Tehran referral hospitals (the capital of Iran). A researcher-made questionnaire with three parts for demographic data, clinical features, and two questions on the choice of the desired location for end-of-life care and the death of cancer patients served as the data collecting instrument. Data were analyzed using SPSS software version 18. The relationship between the two variables preferred place for end-of-life care and death and other variables was investigated using chi-square, Fisher exact test, and multiple logistic regression. Result The mean age of patients participating in the study was 50.21 ± 13.91. Three hundred ninety (69.6%) of the patients chose home, and 170 (30.4%) patients chose the hospital as the preferred place of end-of-life care. Choosing the home as a preferred place for end-of-life care had a significant relationship with type of care (OR = .613 [95% CI: 0.383–0.982], P = .042), level of education (OR = 2.61 [95% CI: 1.29–5.24], P = 0.007), type of cancer (OR = 1.70 [1.01–2.89], P = .049), and income level (Mediate: (OR: 3.27 (1.49, 7.14), P = .003) and Low: (OR: 3.38 (1.52–7.52), P = .003). Also, 415 (75.2%) patients chose home and 137 (24.8%) patients chose hospital as their preferred place of death. Choosing the home as a preferred place of death had a significant relationship with marriage (OR = 1.62 [95% CI: 1.02–2.57], P = .039) and time to diagnostic disease less than 6 months (OR = 1.62 [95% CI: 0.265–0.765], P = .002). Conclusion The findings of the current research indicate that the majority of cancer patients selected their homes as the preferred location for end-of-life care and final disposition. Researchers advise paying more attention to patients’ wishes near the end of life in light of the findings of the current study. This will be achieved by strengthening the home care system using creating appropriate infrastructure, insurance coverage, designing executive instructions, and integration of palliative care in home care services.